Studi Analisis Bank Sperma dan Jual Beli Sperma Menurut Persepektif Hukum Islam - Kunhaniah Mabruroh; Anis Suaidah (Jurnal At Taajir, 2022)
Muamalah is a field of Islamic scholarship in which there are several study materials, including buying and selling, debts, leases, and so on. Including the discussion that the researcher raises in this thesis, namely taking the focus of the study of buying and selling if the fulfillment of a pillar and condition, including the form of the object of the transaction can be known clearly, can be submitted and appreciated. Likewise in the sale and purchase contract which must be carried out based on his own wishes without any coercion from anyone. The research method carried out by the researcher is using the Librari Research method where data collection is carried out by examining and seeking information related to sperm banks and the law of buying and selling sperm from various study sources such as the Qur'an, hadith, ijma' and the opinions of scholars. fiqh experts and scholars. In which free sperm and sperm are traded to anyone in a sperm bank to people who need sperm donors for certain purposes. The formulation of the problem taken by the researcher is: what is the view of Islamic law on sperm banks? And what is the view of Islamic law on sperm buying and selling transactions? In addition, researchers also have goals to be achieved including: to find out the purpose of Islamic law against sperm banks and the law of buying and selling sperm according to Islamic law. Based on the results of the study, it can be concluded that: a sperm bank as a place for sperm donors and storage of frozen sperm fluid and the sale and purchase of sperm is illegal and unlawful because it does not meet the requirements of the pillars of buying and selling and is a sale and purchase that contains many disadvantages.